Cultural intelligence and inclusive leadership in a diverse IT sector: a framework for effective collaboration - Камрун Нахар; Омар Фарук; Захир Райхан (Современные инновации, системы и технологии)
The internationalization of the IT business has created culturally varied teams, which have their own pros and cons.  In the wrong hands, variety may cause conflict, misunderstanding, and time loss. Diversity may inspire creativity and innovation in the right individuals.  This article describes cultural intelligence (CQ) and Inclusive Leadership (IL), which may promote diverse IT team cooperation.  The study draws on previous research and literature to show how team members may utilize CQ to communicate with individuals from diverse cultures and how IL can make everyone feel heard.  The results show that IL methods and strong cultural intelligence boost team performance, employee innovation, and employee happiness in IT contexts.  This essay examines how Innovative Leadership, particularly CQ, empowers IT businesses to innovate and collaborate.  Based on a mixed-methods study with 600 participants from worldwide IT businesses, the paper proposes CQL-IncluNet, a prediction algorithm to model and evaluate collaboration.  Statistics show that CQ and IL interact statistically, explaining 68% of cooperation effectiveness variance.  Regression analysis, interview topic coding, and SEM support this finding.  This study merges theory and practice to fill multicultural team management gaps.  The report recommends concentrated leadership training and AI-based research to promote IT cross-cultural collaboration.